(untitled) (Journal of Plant Disease Sciences, 2017)
Evaluation of different application methods of native Pseudomonas fluorescens against major diseases of rice was carried out during five consecutive seasons of 2012-13, 2013, 2013-14, 2014 and 2014- Rabi Kharif Rabi Kharif Rabi 15 at Rice Research Station, Moncompu, Alappuzha. The diseases including sheath blight, blast, bacterial blight and brown spot of rice.The treatments were seed + Pf seedling dip, seed + soil, seed + seedling + foliar and seed + soil + foliar Pf Pf Pf spray with the standard check fungicide carbendazim.Seed + soil and seed + seedling dip treatments were performed well in reducing the disease severity and visual score. The pooled data of five seasons showed that the native bioformulation Pseudomonas fluorescens as seed + seedling dip or seed + soil application was found superior compared to seed + seedling dip + foliar and seed + soil + foliar application treatment for the effective management of sheath blight, blast, bacterial blight and brown spot disease occurrence in different region of Kuttanad.